P5 dalam Kurikulum Merdeka Tumbuhkan Budaya Riset di Kalangan Pelajar - Agusta, Erna Sari (Madaris: Jurnal Guru Inovatif, 2024)
Research-based learning is an effort to train students' scientific thinking in facing future challenges. The scientific way of thinking also requires students to be literate in order to ward off issues whose truth value is uncertain as well as to shape the character of Pancasila students. To overcome this problem, the government established the Independent Curriculum which implements project-based learning to grow the profile of Pancasila students (P5). This study aims to determine the effect of P5 on research culture among students. The benefit of this research is to motivate madrasa residents to carry out P5 activities well while at the same time stimulating a research culture among students. This research uses a qualitative approach with descriptive methods. The subjects in this study were 7th grade students at MTsN 28 Jakarta, totaling 192 students. The results of the study concluded that P5 learning can foster a research culture among students. However, the achievement in preparing research reports up to Chapter V has only reached 75%. Obstacles in research activities include: lack of confidence, difficulty finding references, lack of interest in reading and lack of time in processing data and making conclusions. Abstrak Pembelajaran berbasis riset merupakan salah satu upaya dalam melatih cara berpikir ilmiah siswa dalam menghadapi tantangan masa depan. Cara berpikir ilmiah juga diperlukan siswa untuk melek literasi guna menangkal isu-isu yang belum pasti nilai kebenarannya sekaligus membentuk karakter pelajar Pancasila. Untuk mengatasi masalah tersebut, pemerintah menetapkan Kurikulum Merdeka yang menerapkan pembelajaran berbasis proyek untuk menumbuhkan profile pelajar pancasila (P5). Penelitian ini bertujuan untuk mengetahui pengaruh P5 terhadap budaya riset di kalangan pelajar. Manfaat penelitian ini adalah memberikan motivasi kepada warga madrasah untuk melaksanakan kegiatan P5 dengan baik sekaligus menstimulasi adanya budaya riset di kalangan pelajar. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Subjek dalam penelitian ini adalah siswa kelas 7 MTsN 28 Jakarta yang berjumlah 192 siswa. Hasil penelitian menyimpulkan bahwa pembelajaran P5 dapat menumbuhkan budaya riset di kalangan pelajar. Akan tetapi, pencapaian dalam penyusunan laporan riset sampai Bab V baru mencapai 75%. Kendala dalam kegiatan riset antara lain: kurangnya rasa percaya diri, kesulitan mencari referensi, kurangnya minat baca dan kurangnya waktu dalam mengolah data dan membuat kesimpulan.